A Large-Scale Sequencing-Based Survey of Plasmids in Listeria monocytogenes Reveals Global Dissemination of Plasmids - Schmitz-Esser, Stephan; Anast, Justin M.; Cortes, Bienvenido W. (Frontiers in Microbiology, 2021)
The food-borne pathogen Listeria monocytogenes is known for its capacity to cope with multiple stress conditions occurring in food and food production environments (FPEs). Plasmids can provide benefits to their host strains, and it is known that various Listeria strains contain plasmids. However, the current understanding of plasmid frequency and function in L. monocytogenes strains remains rather limited. To determine the presence of plasmids among L. monocytogenes strains and their potential contribution to stress survival, a comprehensive dataset was established based on 1921 published genomes from strains representing 14 L. monocytogenes sequence types (STs). Our results show that an average of 54% of all L. monocytogenes strains in the dataset contained a putative plasmid. The presence of plasmids was highly variable between different STs. While some STs, such as ST1, ST2, and ST4, contained few plasmid-bearing strains (<15% of the strains per ST), other STs, such as ST121, ST5, ST8, ST3, and ST204, possessed a higher proportion of plasmid-bearing strains with plasmids found in >71% of the strains within each ST. Overall, the sizes of plasmids analyzed in this study ranged from 4 kbp to 170 kbp with a median plasmid size of 61 kbp. We also identified two novel groups of putative Listeria plasmids based on the amino acid sequences of the plasmid replication protein, RepA. We show that highly conserved plasmids are shared among Listeria strains occurring globally over the last few decades. To investigate potential roles of plasmids, nine genes related to stress-response were selected to assess their abundance and conservation among L. monocytogenes plasmids. The results demonstrated that these plasmid genes exhibited high sequence conservation but that their presence in plasmids was highly variable. Additionally, we identified a novel transposon, Tn7075, predicted to be involved in mercury-resistance. Here, we provide the largest plasmid survey of L. monocytogenes to date with a comprehensive examination of the distribution of plasmids among L. monocytogenes strains. Our results significantly increase our knowledge about the distribution, composition, and conservation of L. monocytogenes plasmids and suggest that plasmids are likely important for the survival of L. monocytogenes in food and FPEs.